IMMOBILIZATION OF ?-AMYLASE ENZYME ON POLY METHYL METHACRYLATE (PMMA) MATRIX - Wiradinata M, Arbi
Activation of poly(methyl methacrylate) (PMMA) is needed to enable the formation of covalent bonds between PMMA and enzymes. In this study, PMMA has been activated using NaOH, H2SO4, and H2SO4- ethylenediamine. Activation with NaOH showed negative result because there was no change in FTIR spectrum before and after activation. Activation was successfully carried out using a 12 M H2SO4 solution at 60? for 2 hours which is indicated by the appearance of a new peak at wavenumber 3401 cm-1 which is